Mons Sanctus Andechs - Kostowski, Jakub (1958-2006). (1996)
Tekst dotyczy wydawnictw publikowanych z okazji roku jadwiżańskiego.
Tytuł nagłówkowy.
Zawiera fotografie.
Keywords: Jadwiga -- (święta ; -- ok. 1179-1243) -- rocznice